Pore characteristics in one-part mix geopolymers foamed by H2O2: The impact of mix design. (15th September 2017) - Hajimohammadi, Ailar; Ngo, Tuan; Mendis, Priyan; Nguyen, Tuan; Kashani, Alireza; van Deventer, Jannie S.J.
Abstract: In geopolymers foamed by H2 O2, it is important to consider the impact of mix design on both geopolymerisation reaction and the H2 O2 foaming reaction to control the porosity of the geopolymer foam matrix. In this paper, the effect of mix design on both reactions is discussed and correlated with the properties of the resulting geopolymer foams. It is found that when the mix design provides a chemically stable environment for the foaming reaction and simultaneously facilitates rapid setting of the binders, it results in homogeneously distributed fine pores within the matrix. The homogeneity of pore distribution is determined by a non-destructive test and correlated with the thermal conductivity results. It is suggested that for better thermal insulating properties, geopolymer foams are preferably poured and cured parallel to the heat flow direction. The size distribution of pores is shown to be a critical parameter in determining the strength of foams, and the mesoscale-based finite element analysis is performed to create a predictive tool for correlating the pore size distribution of geopolymer foams with their mechanical properties. Graphical abstract: Highlights: Higher percentage of sodium silicate in geopolymer mix solution results in more stable H2 O2 decomposition (foaming process). The percentage of open porosity decreases from 58 to 22 vol% as the foaming process becomes more stabilised. Homogeneity of pore distribution increases from 82% to 98% by stabilising the decomposition of H2 O2 . Insulation capacity of metakaolin foams increases by 16% as a result of improved foam homogeneity. The size of the pores has a greater effect on compressive strength compared to the homogeneity of pore distribution.